QUALITY REQUIREMENTS OF THESIS (PROJECT OF MINISTRY OF EDUCATION AND SCIENCE OF UKRAINE): THE PROBLEM OF NORMS AND STANDARDS - Hnatiuk, Mykhailo A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
"Quality Requirements of Thesis " (Project of Ministry of Education and Science of Ukraine 2016 year) was analysed with regard to its efficiency. There was found a number of problems caused by the imperfection of the national bibliographic standards and incompatibility with foreign norms. They were characterized. According to the results of the investigation it is suggested a new steps that can solve these problems.